2014
DOI: 10.1111/aos.12521
|View full text |Cite
|
Sign up to set email alerts
|

The importance of angle kappa evaluation for implantation of diffractive multifocal intra‐ocular lenses using pseudophakic eye model

Abstract: ABSTRACT.Purpose: To determine the critical value of the angle kappa in connection with a higher risk of photic phenomena for the AcrySof ReSTOR and Tecnis multifocal intra-ocular lens (MIOL) on a standardized pseudophakic eye model. To analyse the impact of biometric value changes on the critical angle kappa. Methods: Geometrical optic rules applied to a suitable optical model of the pseudophakic eye were used to calculate the critical value of the angle kappa for the Tecnis and three types of the AcrySof ReS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
52
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 27 publications
2
52
1
1
Order By: Relevance
“…Prakash et al 3 confirm if this range of temporal decentration increases or not the risk of the symptoms as has been hypothesized. 35 We aware that our methodology for evaluating IOL centration has some important limitations in order to precisely measure the centration. The centration was based on a subjective ordinal scale interpretation and the size of the first ring at the corneal plane was assumed to be 1.2 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Prakash et al 3 confirm if this range of temporal decentration increases or not the risk of the symptoms as has been hypothesized. 35 We aware that our methodology for evaluating IOL centration has some important limitations in order to precisely measure the centration. The centration was based on a subjective ordinal scale interpretation and the size of the first ring at the corneal plane was assumed to be 1.2 mm.…”
Section: Discussionmentioning
confidence: 99%
“…At this point, angle kappa has great importance to understand and use the optical principles involved with these complications . Studies have revealed that if angle kappa is large (≥ 0.6 mm), a high percentage of subjective complaints occur regarding halos and glare even with proper centration of the intraocular lens . Therefore, evaluation of angle kappa before refractive surgery (both corneal and lenticular) has gained significant importance.…”
Section: Discussionmentioning
confidence: 99%
“…Visual axis is the line connecting the fixation point with the fovea. Each eye has a different angle kappa, usually less than five degrees …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…New technologies based on small aperture corneal inlays (small disks with about 1.6‐mm inner aperture) generated a new challenge to locate an optimal position in the cornea for implanting the inlay. The sensitivity to the centration of the inlays evoked numerous speculations – from “no influence” to “critical role” . Tabernero and Artal showed, by using numerical simulations with data from real eyes, that a decentration of 0.4 mm from a previously estimated optimal point could noticeably decrease the image quality.…”
Section: Discussionmentioning
confidence: 99%